Characterisation of Co/Mn catalysts synthesised via reverse microemulsion method. (8th December 2014) - Zabidi, N. A. Mohd; Pilus, R.; Rahman, S.; Ali, S.
<x content-type="archive" xml:space="preserve">Abstract</x> The objective of this work is to investigate the effects of manganese on the morphology and reducibility of cobalt catalyst. A series of Co/Mn catalyst was prepared via a reverse microemulsion method on a SiO2 support. The metal loading was kept at 10 wt-%. The Mn/Co mol ratio was set at 0, 0·05, 0·12 and 0·25. Based on the transmission electron microscopic analyses, the average particle size of the catalyst was found to be in the range of 3–5 nm for the different catalyst formulation. The presence of up to 12 mol-% Mn enhanced the reducibility of the Co-based catalyst. The catalytic activity in the Fischer-Tropsch reaction varied with the content of Mn in the Co-based catalyst. The highest CO conversion (20·5%) and C5+ selectivity (12·6%) were obtained using the 88Co12Mn/SiO2 catalyst.